1993
DOI: 10.1520/jfs13509j
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Sex Offender and Offense Traits by Victim Age

Abstract: The authors studied offender, offense, and victim characteristics according to victim age cohort among a sample of over 800 incarcerated sex offenders. Their findings were somewhat different from those previously reported, and suggest that rapists of adults were more psychopathic, sexual assailants against adolescents appeared to be more typical family men, and child molesters were more opportunistic chronic sex offenders. The authors believe their findings begin to shed light on the nature of sex crimes commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
2
11
1
Order By: Relevance
“…However, these findings continue to follow the pattern of results and the larger literature that rapists and general offenders are often similar with the exception of a sexual crime. As the literature suggests, rapists tend to be more antisocial and generally criminal and the data in this sample support these assertions (Harry et al, 1993;Seto & Barbaree, 1999;Simon, 2000). As Reid, Wilson, and Boer (2011) conclude, "… rapists are not specialized in the type of crime they commit.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, these findings continue to follow the pattern of results and the larger literature that rapists and general offenders are often similar with the exception of a sexual crime. As the literature suggests, rapists tend to be more antisocial and generally criminal and the data in this sample support these assertions (Harry et al, 1993;Seto & Barbaree, 1999;Simon, 2000). As Reid, Wilson, and Boer (2011) conclude, "… rapists are not specialized in the type of crime they commit.…”
Section: Discussionsupporting
confidence: 63%
“…Seto and Barbaree (1999) found that rapists scored higher than child molesters on the PCL-R, indicative of more psychopathic features (e.g., antisocial behaviors, poor behavior controls, impulsivity, criminal versatility). Additionally, Harry, Pierson, and Kuznetsov (1993) found that rapists tend to be more antisocial and to have committed more acts of impersonal violence. Further, the researchers described them as resembling general population inmates or "ordinary" criminals.…”
mentioning
confidence: 99%
“…However, as indicated, research has clearly demonstrated that certain conditions, such as offense planning and organization (Davies, Wittebrood, & Jackson, 1998;Kuznetsov et al, 1992) and aggressiveness (Guay, Ouimet, & Proulx, 2004;Harry et al, 1993) moderate this relationship.…”
Section: Victim-offender Age Relationshipmentioning
confidence: 97%
“…Research across a range of sex offenders has consistently demonstrated evidence of a negative linear correlation between the age of the victim and the age of the offender (Gebhard et al, 1965;Grubin & Kennedy, 1991;Harry, Pierson, & Kuznetsov, 1993;Kuznetsov, Pierson, & Harry, 1992). Accordingly, researchers have found stable victim age preference in the majority of serial sexual offenders (Christie, Marshall, & Lanthier, 1979;Guay, Proulx, Cusson, & Ouimet, 2001;Henn, Herjanic, & Vanderpearl, 1976).…”
Section: Victim-offender Age Relationshipmentioning
confidence: 99%
See 1 more Smart Citation